Common issues of poetry in karakalpak literary criticism (1990-2000) - Allanazarova Zukhra Jannazarovna (International Journal Of Literature And Languages, 2025)
General common issues of poetry were comprehensively discussed from a scientific point of view in the Karakalpak literary criticism of the 1990s. The article covers literary criticism materials published in the Republic of Karakalpakstan in 1990-2000 in the magazine "Amudarya" and newspapers "Erkin Qaraqalpaqstan," “Qaraqalpaqstan jasları”, “Ustaz jolı”.